Gendered-Analysis on Research Competency of 21st Century Learners - Camara, Jun S.; Cancino, Edwin C.; Rahon, Christy Ann M.; Terre, Elsa Q.; Ventayen, Randy Joy M.; Quibilan, Mary Jane U.; Urbano, Jomar M. (The journal of contemporary issues in business and government, 2021)
Gender influence on research competency, though important, is less explored compared with other academic disciplines. This study aimed to compare both genders in their perceived level of research competency. The study utilized a descriptive-status research design which employed a validated survey questionnaire administered digitally all over the Philippines from October to November 2020. Participated in by 1, 220 participants from 9 regions and 27 provinces in the Philippines, the study revealed that both genders consider themselves as ‘Highly Competent’ in research, with the female respondents more competent than the male respondents in terms of writing. Findings revealed areas of strength and weaknesses in research instruction and national and international implications for these findings were noted. The authors recommended several measures to address these issues.